“Same Old Ed, . . . Uncommitted”: BMW Socialism and Post-Roguery in Guy Vanderhaeghe’s Early Fiction - Bolay, Jordan (Text Matters: A Journal of Literature, Theory and Culture, 2019)
In this paper I assess how Guy Vanderhaeghe’s early fiction criticizes the class-based and civil movements of post-1960s Saskatchewan through the recurring character of Ed. The protagonist of “Man Descending” and “Sam, Soren, and Ed” from Man Descending, the uncollected “He Scores! He Shoots!” and the novel My Present Age, Ed both condemns and epitomizes the contaminated and seductive gestures of the movements’ influences and enterprises. Vanderhaeghe deploys layers of social criticism: the first comments on the new urban progressive generation—the BMW socialists—while another manifests a counter-criticism that comments on those who challenge social progress, questioning their motives and the credibility of their critique. But what is a BMW socialist? A sociopolitical chameleon hiding behind pretense? Ed describes such a creature as a former “nay-sayer and boycotter” who “intended to dedicate his life to eternal servitude in a legal-aid clinic,” but then “affluence did him in” and now “his ass [is] cupped lovingly in the contoured leather seats of his BMW” (Man Descending 237–38). Vanderhaeghe’s early works criticize the contemporary middle class and progressivist movements of the second half of the twentieth century through this sociopolitical rogue—who in turn becomes a post-rogue. For Ed is ironically undercut by a counter-narrative that is often sub-textual, resulting in a fascinating appraisal of social ignorance, immobility, and unproductivity rather than of any specific ideology.